Sochi/Сочи 2014: Olympic Winter Games between High Mountains and Seaside - Kurt Scharr; Ernst Steinicke; Axel Borsdorf (Revue de Géographie Alpine)
The IOC’s decision to accept Sochi’s bid to host the 2014 Olympic Winter Games presented the Russian Government with an opportunity for international repositioning. The Caucasian War in August 2008, too, can be linked to this development. Going back to the very beginnings of the Soviet Republic, the Sochi region has achieved the tradition of a resort for health and recreation. However, these functions have so far just concentrated along the Eastern Black Sea’s narrow shoreline. With regard to tourism, the 2014 Games will extend the business segment by establishing the new winter season, whereby the planned actions and measures taken will reach extreme and superlative dimensions. From this perspective, an analytical observation systematically accompanying this mega sports event even prior to its commencement will be of exceptional importance. The academic literature pertaining to the Southern part of the Western Caucasian region shows a noticeable lack of contributions in regards to emerging changes. The study focuses on aspects of regional planning and settlement, as well as on socio-economic developments. Further questions posed at the same time relating to society as a whole refer to social processes of participation and decision-making. Overall, the current transformation processes that have reached this area in 1991 will therefore accelerate significantly. The effectiveness as well as the political willingness to promote societal bottom-up processes will in the end prove to be a measuring stick of their own sustainability.